Foresight methods and SAMIS related decision support scenarios development. Final report - Peou, Rathana; Verkuil, Loes; Duden, Anna; Vervoort, Joost M.; Verweij, Pita; Petri, Monica; Photiyalay, Vandy (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This report aims to provide an overall understanding of the advanced course main learning objectives, e-seminars structures and outputs. It presents the scenarios and visuals developed by the participants through the advanced course.